39 Spatial single-cell quantitative analyses of human head and neck squamous cell carcinomas. (9th November 2020) - Blise, Katie; Sivagnanam, Shamilene; Coussens, Lisa; Goecks, Jeremy
Abstract : Background: While the quantities and types of immune, tumor, and structure-related cells present in the tumor-immune microenvironment (TiME) are important for understanding aspects of cancer progression and potential responses to therapy, spatial locations and relationships of these cells also play a critical role. Emerging single-cell imaging modalities, such as multiplex immunohistochemistry (mIHC), provide phenotypic and functional state information for each cell present in the TiME while maintaining the spatial context of tissue architecture. We performed a quantitative analysis of mIHC images to characterize the cellular composition and spatial organization of human head and neck squamous cell carcinomas (HNSCC) and identified features correlated with patient survival. Methods mIHC is an immunoassay-based imaging platform that evaluates sequentially stained immune lineage epitope-specific antibodies for immunodetection on FFPE tissue sections to phenotype single cells as tumor, stromal (mesenchymal), or one of more than 20 different immune cell lineages, all while maintaining the Cartesian coordinates of each cell. 1 2 Matched primary and recurrent HNSCC tumors from nine patients were assayed via mIHC. Using unsupervised hierarchical clustering and principal component analysis, we interrogated the heterogeneity in cellular composition of each tumor section. We further quantified the spatial organization of tumors and identified prognostic tumor and immune cell architectures, 3 as well as cellular neighborhoods that clustered together based on similar compositions and physically grouped together to reveal common spatial features across tumors. Results: Regions from the same tumor and tumors from the same patient clustered together more in their cellular composition than tumors from different patients. We also observed a decrease in the fraction of B cells present in recurrent tumors following therapy for all patients (p=0.024). While common biomarkers for HNSCC, such as CD8+ T cell density and tumor cell abundance were not associated with outcome, the tumor-immune spatial relationship was prognostic. Tissue regions of compartmentalization between immune and tumor cells were associated with higher fractions of αSMA+ stromal cells and had a greater proportion of Ki-67+ lymphocytes present, as compared to mixed regions. Patients with more compartmentalization in their primary tumors demonstrated longer progression free survival than those with more mixing between these cell types (p=0.027). Conclusions: Our results provide insight into the spatial organization of HNSCCs, highlighted by the result that compartmentalization between immune and tumor cells is associated with improved outcomes. This study provides spatial analysis methods and hypotheses that can be used as a framework for analysis of larger cohorts. Ethics Approval: This study was approved by Oregon Health and Science University's IRB (protocol #809 and #3609), and written informed consent was obtained. References: Tsujikawa T, et al. Quantitative multiplex immunohistochemistry reveals myeloid-inflamed tumor-immune complexity associated with poor prognosis. Cell Rep 2017;19:203–217. Banik G, et al. High-dimensional multiplexed immunohistochemical characterization of immune contexture in human cancers. Methods Enzymol 2020;635:1–20. Keren L, et al. A structured tumor-immune microenvironment in triple negative breast cancer revealed by multiplexed ion beam imaging. Cell 2018;174:1373–1387.